Business model maturity in management theory and practice - defining from an expert perspective - Niewiadomski, Przemysław (Zielona Góra: Faculty of Economics and Management Press)
Since many researchers and managers think about the essence, creation mechanisms and limits of the manufacturing model maturity, at this point, the author raises the question related to this issue: what dimensions (descriptions and desiderata) should be considered when conceptualizing this idea?
Keywords: business model; maturity; opportunity; mature business model; model biznesu; dojrzałość; okazja; dojrzały model biznesu